ASSOCIATION BETWEEN LOW BIRTH WEIGHT (LBW) INFANTS AND TH INCIDENCE OF ACUTE LEUKEMIA IN CHILDREN - Roidlotul Nikmah Annafi; Yetty Movieta Nancy; Mulyono Mulyono; Dwi Retnoningrum (Faculty of Medicine, Diponegoro University, Semarang, Indonesia, 2020)
Background: Acute leukemia is a blood cells malignancy disease originating from the bone marrow, characterized by the proliferation of white blood cells, with manifestations of abnormal cells in peripheral blood. Perinatal conditions such as low birth weight can increase the risk of leukemia in children. Low birth weight infants cause resistance towards GH and IGF-1 which triggers leukemia. The purpose of this study is to determine the correlation between low birth weight infants and the incidence of acute leukemia in children. Methods: A case-control analytic observational study, carried out at RSUP Dr. Kariadi. The study was conducted in July-October 2019. Subjects were patients with acute leukemia as the case group and non-leukemia patients as the control group aged 0-18 years old. Data was collected by interview using a questionnaire and then data analysis was conducted using the chi square test. Results: Research subjects 82 people, aged 0-18 years old consisting of 46 males (56.1%) and 36 females (43.9%). No significant relationship was found between low birth weight infants with the incidence of acute leukemia in children. Different results were obtained for the duration of breastfeeding with the incidence of acute leukemia in children with P = 0.002. Conclusion: There was no association between low birth weight (LBW) infants and the incidence of acute leukemia in children.Keywords: acute leukemia in children, LBW